A Struggle for Survival: Meaning of Late Life in a Rural District in Uganda: A Qualitative Study - Knizek, Birthe Loa; Vancampfort, Davy; Kwiringira, Japheth; Kyazike, Elizabeth; Mugisha, James (Frontiers in Psychology, 2021)
Background: Between 2015 and 2050, the aging population of Uganda (aged 50 years and older) will be nearly doubled. Therefore, later-life problems have become an area of increasing research and policy interest. This study aimed at exploring how aging people living in extreme poverty in a low-income country experience their everyday life and what kind of meaning systems employed by them to understand and cope with their living conditions. Methods: We conducted a qualitative interview with 14 participants in the Buikwe district. In this interview, 11 women and 3 men were included, and a thematic analysis was employed for data processing and analysis. Results: Unanimously, all participants reported their condition as extreme poverty. The key informants (KIs) emphasized respect from descendants and the community as a foundation for a meaningful later life. In contrast, this aspect has been ever mentioned by no caregivers but by only one care-receiver. The willingness/ability of children to support the elderly who are in need of support formed a major part of the reflections of care-receivers, which would be decisive for their position in the society and the respect they would receive. In addition, both Christianity and traditional beliefs as well as beliefs in witchcraft and ancestral spirits were employed as a basis for actions and reflections. Discussion: The question arises whether life in extreme poverty conditions can be perceived as meaningful. Respect was mentioned as fundamental by the KIs, thereby giving priority to social relations as the most meaningful factor for living a meaningful life. The ability and willingness of the possible descendants for support as the focus of care-receivers might be a more down-to-earth description of this aspect but without using the same level of abstraction. For the majority, due to their belief system did not serve as a source of consolation their main focus was on social relationships for support. To improve the wellbeing of the old people, their sense of meaning must be restored through a system, guaranteeing the coverage of basic needs and measures to restore dignity through a reintegration in both community and congregations. Social service agencies who are targeting the elderly people need to work toward this objective.